Homeless bird - Whelan, Gloria (New York : HarperTrophy, 2001)
When thirteen-year-old Koly enters into an ill-fated arranged marriage, she must either suffer a destiny dictated by India's tradition or find the courage to oppose it.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
4.1
3-6
Keywords: Courage -- Fiction; Courage -- Fiction; India -- Fiction; India -- Social life and customs -- Fiction; India -- Fiction; India -- Social life and customs -- Fiction